Abstracts reporting of HIV/AIDS randomized controlled trials in general medicine and infectious diseases journals: completeness to date and improvement in the quality since CONSORT extension for abstracts. Issue 1 (December 2016) - Bigna, Jean; Noubiap, Jean; Asangbeh, Serra; Um, Lewis; Sime, Paule; Temfack, Elvis; Tejiokem, Mathurin
Abstract Background Sufficiently detailed abstracts of randomized controlled trials (RCTs) are important, because readers often base their assessment of a trial solely on information in the abstract. We aimed at comparing reporting quality of RCTs in HIV/AIDS medicine before and after the publication of the 2008 CONSORT extension for abstracts and to investigate factors associated with better reporting quality. Methods We searched PubMed/Medline for HIV/AIDS RCTs published between 2006–07 (Pre-CONSORT) and 2014–15 (Post-CONSORT) in 40 leading general medicine and infectious diseases journals. Two investigators extracted data and scored abstracts. The primary outcome was the adjusted mean number of items reported among the 17 required. Proportions of abstracts reporting each of 17 items were considered as secondary outcome. The adjustment was done for journal field, CONSORT endorsement, abstract format, type of intervention, journal impact factor and authorship. This study received no funding. Results The adjusted mean number of reported items was 7.2 (95 % CI 6.6–7.7) in pre-CONSORT (n  = 159) and 7.8 (95 % confidence interval [CI] 7.3–8.4) in post-CONSORT (n  = 153) (mean difference 0.7; 95 % CI 0.1–1.2). Journal high impact factor (adjusted incidence rate ratio 2.16; 95 % CI 1.83–2.54), abstract with 13 authors or more (1.39; 95 % CI 1.07–1.79) and non-pharmacological intervention (1.19; 95 % CI 1.03–1.37) were independent factors for better reporting quality. There were significant improvements in reporting on participants, randomization, outcome results, registration and funding; regression for author contact; and no change for other items: title, design, interventions, objective, primary outcome, blinding, number randomized, recruitment, number analyzed, harms and conclusions. Conclusions After the publication of the CONSORT extension for abstracts, the reporting quality of HIV/AIDS RCT abstracts in general medicine and infectious diseases journals has suboptimally improved. Thus, stricter adherence to the CONSORT for abstract are needed to improve the reporting quality of HIV/AIDS RCT abstracts.